A positive trait-mediated indirect effect involving the natural enemies of competing herbivores. - van Veen, F; Brandon, C; Godfray, H (2009)
Trait-mediated indirect effects can have important effects on food web dynamics but are still poorly understood in the field. In a previous population cage study of a small community of aphids and an aphid natural enemy it was found that a trait-mediated indirect effect involving the natural enemy's behaviour was key to understanding community persistence. Here evidence is presented that a related phenomenon involving some of the same species occurs in the field. Surveys showed that two species of aphid (Acyrthosiphon pisum and Megourella purpurea) tended to share a host plant with a third generally unpalatable species (Megoura viciae) more often than expected by chance. Further evidence suggested this was not due to differential plant suitability or location, but to a positive effect of M. viciae on the performance of the other two species. To test this, field experiments were set up comparing the size and persistence of A. pisum colonies sharing or not sharing a plant individual with M. viciae colonies. A. pisum colonies tended to be larger and persisted for a longer period of time in the presence of M. viciae, an effect that was significant for small colonies exposed to many predators. When protected from predation the presence of M. viciae had no effect on A. pisum colonies. The positive effects of M. viciae on A. pisum is thus likely to be natural-enemy mediated rather than plant mediated. How predation by Syrphidae, the major group observed in the study, is affected by M. viciae is discussed.